Strategi Pengelolaan Keuangan Sekolah Untuk Meningkatkan Efisiensi Sumber Daya - Dini Melinda Ayu; Re Girindratta; Nida Nurfadillah; Firyal Fariz; Malki Al Mashur (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Effective and efficient financial management in schools is a key factor in ensuring operational continuity and enhancing the quality of education. Good financial management helps schools achieve educational goals by maximizing the use of available funds. The main challenges faced in school financial management include limited funding, improper budget allocation, and a lack of transparency and accountability. This study aims to explore financial management strategies that can be implemented by schools to improve the efficiency and effectiveness of resource use. Using a literature study approach, this research finds that comprehensive budget planning, managerial capacity building, adoption of information technology, stringent internal monitoring and auditing, and diversification of funding sources are some of the strategies that can be implemented. It is hoped that with the implementation of these strategies, schools can manage finances better and support quality education programs.